VOLATILITY OF VOLUME IMPORTS OF MAJOR FOOD COMMODITIES IN INDONESIA - Adrian D Lubis; Dian V. Panjaitan (Universitas Islam Indonesia, 2012)
Abstract The purpose of this study is to determine the impact of an increase in the volume of imports and import tariff on domestic prices. The method used in this study are ARCH, GARCH, VECM, and OLS using the data of import volume of Indonesia and Indonesia's domestic market prices during the period June 2007 until March 2011. The result shows that there is an increasing volume of imports which might increase the price of rice, wheat, milk, and sugar in the domestic market. The paper also finds that an increase in import tariff on these commodities lowers prices in the domestic market. Keywords: Volatility, import tariff, import volume JEL classification numbers: F13, F14Abstrak Tujuan penelitian ini adalah untuk mengetahui dampak peningkatan volume impor dan tarif impor pada harga domestik. Metode yang digunakan adalah ARCH, GARCH, VECM, dan OLS menggunakan data volume impor Indonesia dan harga pasar domestik Indonesia selama periode Juni 2007 sampai Maret 2011. Hasil penelitian menunjukkan bahwa peningkatan volume impor dapat meningkatkan harga beras, gandum, susu, dan gula di pasar domestik. Penelitian ini juga menyatakan bahwa peningkatan tarif impor atas komoditas ini akan menurunkan harga di pasar domestik.Kata kunci: Volatility, tariffs import, volume import JEL classification numbers: F13, F14